2020
DOI: 10.1186/s13071-020-04362-1
|View full text |Cite
|
Sign up to set email alerts
|

Vectors, molecular epidemiology and phylogeny of TBEV in Kazakhstan and central Asia

Abstract: Background In the South of Kazakhstan, Almaty Oblastʼ (region) is endemic for tick-borne encephalitis, with 0.16–0.32 cases/100,000 population between 2016–2018. The purpose of this study was to determine the prevalence and circulating subtypes of tick-borne encephalitis virus (TBEV) in Almaty Oblastʼ and Kyzylorda Oblastʼ. Methods In 2015 we investigated 2341 ticks from 7 sampling sites for the presence of TBEV. Ticks were pooled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…ticks, but it was reported that Dermacentor reticulatus also might play a relevant role as a TBEV nature reservoir [ 38 ]. Moreover, TBEV was detected in pools of Haemaphysalis punctata [ 39 ] and other Haemaphysalis spp. [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…ticks, but it was reported that Dermacentor reticulatus also might play a relevant role as a TBEV nature reservoir [ 38 ]. Moreover, TBEV was detected in pools of Haemaphysalis punctata [ 39 ] and other Haemaphysalis spp. [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sequencing of E-genes of the virus revealed that Kazakh TBEV samples belong to two different clades of the Siberian subtype ( Figure 1D ). Three endemic tick species are responsible for the transmission of the virus ( 18 ). The results of these investigations were recognised by the Ministry of Health in Nur-Sultan.…”
Section: Scientific Output Of the Projectmentioning
confidence: 99%
“…Through the German Federal Foreign Office's German Biosecurity Program, the Bundeswehr Institute of Microbiology (BIM) and the Deutsche Gesellschaft für Internationale Zusammenarbeit GmbH (GIZ) have managed a project in Kazakhstan for the past seven years in collaboration with key Kazakh partners including the aforementioned NSCEDI at the CRL and the Research Institute for Biosafety Problems (RIBSP). Under the auspices of the G7 Global Partnership against the Spread of Weapons and Materials of Mass Destruction, the GBP focuses on surveillance, detection and diagnostics, biosafety and biosecurity including work published on Crimean Congo haemorrhagic fever, tick-borne encephalitis virus, Rickettsia and orthohantaviruses (9)(10)(11)(12).…”
Section: Cooperative Biological Research Programs In the Republic Of Kazakhstanmentioning
confidence: 99%